Eugenia L. (Myrtaceae) no estado do Ceará - Lima, Igor Gonçalves (2023)
Eugenia L. (Myrtaceae) stands out as the richest genus of Angiosperms in the Brazilian flora, with species of high ornamental, food and pharmacological potential. It is also important in the floristic composition of Cerrado, Restinga and Wet Forests, mainly in the Atlantic Forest. It is characterized by having generally tetramerous flowers, no extension of the hypanthium above the ovary, bilocular multiovulate ovary and eugenioid type embryo (cotyledons fused into a solid and homogeneous mass). Despite it’s importance and representativeness, there are no taxonomic studies on the genus in Ceará state, which are extremely necessary as support for more applied and conservation studies. Based on this, the objective of this study was carry out the taxonomic survey of Eugenia in Ceará, in order to provide a better understanding of the floristic diversity of genus in the state. Field expeditions were carried out to collect representatives of the genus in Ceará’s territory, and specimens deposited in national herbaria were analyzed, identified and described. A total of 34 species of Eugenia were registered for Ceará, of which 22 are new records. Identification key, illustrative plates of the species, distribution maps, comments and information on common names, flowers and fruits were provided. Also a new endemic species of Northeast of Brazil was described, named Eugenia nordestina L.R.V.Santos & I.R.Costa. There is a need for greater sampling effort for the group in the state, since many species have scarce specimens or insufficient information for a better analysis, something which should be better elucidated with new collections of Eugenia in Ceará.